Gene editing in an international context Scientific, economic and social issues across sectors - Shukla-Jones, Anu (OECD Science, Technology and Industry Working Papers, 2018)
Gene editing techniques represent a major advance in the field of biotechnological research and application, promising significant benefits across the domains of human health, sustainability and the economy. There is broad agreement that gene editing techniques go beyond incremental advances of past biotechnologies. However, harnessing the potential of gene editing techniques will require meeting significant policy challenges in arenas of governance, ethics, and public engagement. This report summarises the discussions of a group of international experts of science, technology and policy, as well as policymakers at a dedicated workshop entitled "Gene editing in an international context: scientific, economic and social issues across sectors" in Ottawa, Canada on 29-30 September 2016